College student’s social anxiety: a study of the young people mental health in digital age - Cahyaning Suryaningrum (Jurnal Konseling dan Pendidikan, 2021)
Purpose of this study is to analyze whether in the current era social anxiety problems are still developing among college students and whether there are any differences in the level of social anxiety was based on the year of entry (new college students - old college students) and gender. This research is a quantitative-descriptive and comparative studies. Hypotheses are there is no difference in social anxiety level based on the year of entry nor gender. The subjects are undergraduate college students totaled 364 people. Instrument used for data collection is Liebowitz Social Anxiety Scale-Self Report (LSAs-SR). Results showed that 76.9% of the subjects experienced social anxiety. There is no difference in the level of social anxiety among new college students and old college college students nor between male college students and college students.